2016
DOI: 10.1071/mf14109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of aquatic macroinvertebrate diversity in irrigated rice fields and wetlands through different spatial scales: an additive partitioning approach

Abstract: The role of rice fields as refuges for wetland macroinvertebrates was assessed at multiple spatial scales, and macroinvertebrate diversity was compared between fields and natural wetlands. Because irrigated rice fields are highly disturbed environments, and have lower environmental complexity and heterogeneity in the irrigated phase than do wetlands, we hypothesised that the fields would sustain lower diversity than do wetlands, especially at broader spatial scales. Wetlands and rice fields from three regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
1
9
1
2
Order By: Relevance
“…During the sampling period, sensitive organisms to environmental changes, such as Ephemeroptera (Kerans & Karr, 1994) were not found in the conventional systems, which corroborates data of Pires et al (2015).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…During the sampling period, sensitive organisms to environmental changes, such as Ephemeroptera (Kerans & Karr, 1994) were not found in the conventional systems, which corroborates data of Pires et al (2015).…”
Section: Resultssupporting
confidence: 77%
“…The abundance of benthic macroinvertebrates was higher (p<0.05) in the natural wetland than in the cultivated fields, which is opposite to what was reported by Pires et al (2015), who evaluated irrigated rice farmings during the crop season, and reported drought problems at the time of the study. In the present work, abundancy in the site of the organic farming was higher (p<0.05) than in the conventional one, in accordance with the results obtained by Wilson et al (2008) during the crop season.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…; Pires et al . ). Different life‐history strategies occur in freshwater insects in relation to habitat drying, and these include presence of diapause and changes in the life cycle (Batzer & Wissinger ; Verberk et al .…”
Section: Discussionmentioning
confidence: 97%